Literatur Riview Tentang Menumbuhkan Minat Berwirausaha Mahasiswa Prodi Kesehatan di Perguruan Tinggi - Ucha Indra Gunawan (EBISMAN eBisnis Manajemen, 2025)
Entrepreneurial interest has increased significantly in recent years among both the general public and university students. This trend has encouraged higher education institutions to integrate entrepreneurship education into almost all academic programs. One group that has gained increasing attention in entrepreneurship studies is students of health-related programs, such as midwifery, nursing, and pharmacy, as these fields offer substantial opportunities for the development of health-based services and products. Although many studies have focused on entrepreneurial interest among health students, the research methods, variables, and findings vary considerably. Therefore, a comprehensive literature review is needed to synthesize existing research and provide a clearer understanding of entrepreneurial interest within this population. This study aims to review and summarize 15 selected studies examining entrepreneurial interest among students in health-related study programs. A literature review method was employed by analyzing research objectives, theoretical frameworks, research designs, variables, and key findings of the selected studies. The results of this review indicate that entrepreneurial interest among health students is influenced by several factors, including entrepreneurial motivation, knowledge and skills, self-efficacy, social environment, and institutional support. The findings are expected to serve as a reference for higher education policymakers and future researchers in developing more effective and contextually relevant entrepreneurship education strategies for students in the health sector.